Implementasi Digital Marketing Communication Pada Toko Grosir “Dapur Pintar” Dalam Meningkatkan Penjualan - Novriansyah; Salas, Hagi Julio; Marini, Marini (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2025)
The development of digital technology has transformed the dynamics of the retail and wholesale sectors, including how businesses promote products and interact with consumers. This study aims to analyze the implementation of digital marketing communications at Dapur Pintar Wholesale Store and its impact on increasing sales. The study used descriptive qualitative methods through in-depth interviews with store owners and regular customers, as well as direct observation of marketing activities via WhatsApp, Instagram, Facebook, and TikTok. The results show that Dapur Pintar implements promotional messages that focus on affordable prices, product quality, and visual content to attract consumer attention. WhatsApp is the most effective channel for driving conversions due to its personalized communication and rapid response. Instagram and Facebook serve as digital catalogs that strengthen awareness and purchase intention, while TikTok plays a significant role in expanding reach through viral content. However, several challenges were identified, such as inconsistent admin responses, suboptimal visual quality, price comparisons between stores, and complex inventory management. Overall, the digital marketing communications strategy contributed significantly to Dapur Pintar's sales growth.